Brief Measures to Screen for Social Anxiety in Adolescents. Issue 8 (October 2015) - Garcia-Lopez, Luis J.; Sáez-Castillo, Antonio J.; Beidel, Deborah; La Greca, Annette M.
ABSTRACT: Objective: Social anxiety disorder (SAD) in adolescents is considerably underdetected and undertreated despite the availability of efficacious treatments. Our main study objective was to examine brief, valid, and reliable screening measures for adolescent social anxiety, and to then conduct diagnostic interviews to evaluate the measures' ability to identify adolescents with SAD. Methods: We examined 7 brief and valid social anxiety measures and compared their diagnostic accuracy with diagnoses established by a semistructured interview. The sample included 421 Spanish adolescents with and 613 without a clinical diagnosis of SAD. Results: Data revealed that short social anxiety measures are accurate in detecting Spanish-speaking socially anxious adolescents. All questionnaires showed good or excellent discriminating ability, with the Social Anxiety Scale for Adolescents (SAS-A) and the Social Phobia and Anxiety Inventory-Brief (SPAI-B) having the best sensitivity and specificity values, respectively. Excellent areas under the receiver operating characteristic curves were found for most measures, except for the Liebowitz Social Anxiety Scale for Children and Adolescents and the Mini-Social Phobia Inventory, which had good discriminatory ability. There was little statistical difference in the ability of the brief social anxiety measures to identify cases accurately, although the SPAI-B cutoff score yielded the best balance between sensitivity and specificity and the highest Youden Index. Conclusion: Overall, results suggest that brief measures for social anxiety symptoms can be effective in detecting SAD in Spanish-speaking adolescents. Depending on the purpose of the study, SAS-A may be especially useful for reducing false negatives and the SPAI-B for false positives.